Investigation of the key parameters for gas sensing through comparison of electrospun and sol-gel semiconducting oxides. Issue 14 (15th July 2022) - Fioravanti, Ambra; Morandi, Sara; Pedrazzo, Alberto Rubin; Cecone, Claudio; Manzoli, Maela; Zanetti, Marco; Bracco, Pierangiola; Mazzocchi, Mauro; Lettieri, Stefano; Marani, Pietro; Carotta, Maria Cristina
Abstract: The present study aims to highlight the parameters that mostly characterize the efficiency of chemo-resistive effects in semiconductor metal oxides used for gas sensing. To this goal, samples and gas-sensing devices were prepared based on nanostructured ZnO, SnO2 and TiO2 powders, these being the materials on which most chemical sensors are based. Samples were synthesized by both electrospinning technique and sol-gel route. The materials were characterized in terms of textural, structural and morphological properties. Electrical and gas sensing measurements were performed on thick films obtained from the different materials, putting in evidence the relationships with the powder characteristics. The fibers obtained by electrospinning technique revealed to be constituted by spherical particles, which characterize the sol-gel materials as well. In particular, regardless of the synthetic method, the materials are constituted by particles that are aggregates of crystalline domains and the specific surface areas exposed correlate with the dimensions of these aggregates, rather than with the crystallite sizes. Fundamental electrical behaviours were found for the different materials, irrespective of the synthetic procedure. Sensing tests, performed by using different gases, such as carbon monoxide, acetone and isoprene, show that, within the same material, the best performances are obtained with the highest specific surface area.